Education Policy as a Recursive System of Gendered Power: Evidence from Post-2021 Educational Restrictions in Afghanistan - Bibi Zainab Nasiri (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
This study examines how education policy in Afghanistan operates as a system of gendered power following the 2021 policy restrictions, focusing on how these policies shape educational access, lived experiences, and adaptive responses among girls. The study employs a qualitative multi-level design, integrating semi-structured interviews with female students and teachers alongside documentary analysis of policy measures and international reports. Data were analyzed using reflexive thematic analysis supported by cross-source triangulation. The findings reveal that education policy functions as a recursive system in which institutional inequality and religious legitimation reinforce one another, producing psychological and socio-economic consequences. At the same time, participants demonstrate adaptive and resistant forms of agency, including informal and community-based learning practices. These dynamics indicate that exclusion, experience, and resistance are co-constitutive rather than sequential processes. The study contributes to theory by advancing a multi-level framework linking policy, lived experience, and agency. However, the relatively small sample size and limited access to policymakers constrain broader empirical generalization. This study offers a novel conceptualization of education policy as a recursive system of gendered power. By integrating social justice, community empowerment, and policy analysis, it provides a theoretically grounded and empirically supported framework for understanding educational exclusion in restrictive contexts.